Minimizing Nitrate Reduction during Kjeldahl Digestion of Plant Tissue Extracts and Stem Exudates : APPLICATION TO (15)N STUDIES - Pace, Gary M. (1982)
From 10 to 60% of the nitrate present in plant tissue extracts and stem exudates of corn (Zea mays L.) was found to be reduced during Kjeldahl digestion, even in the absence of added reducing agents. This reduction is of particular concern in [(15)N]nitrate assimilation studies, because it results in an overestimate of nitrate reduction. To overcome this problem, a method was developed for removing nitrate prior to Kjeldahl digestion, thereby preventing nitrate reduction. The procedure utilizes hydrogen peroxide for partial oxidation of organic matter in order to minimize the nitration of organic compounds. The free nitrates are then volatilized as nitric acid from concentrated sulfuric acid at 95°C. When the proposed method was used as a pretreatment to Kjeldahl digestion, less than 0.5% of the applied nitrate was recovered in the reduced nitrogen fraction of plant tissue extracts and stem exudates.